Marketing and Exchange of Farm Products in Facebook Groups: A Case Study - Asha Vijay, T.; Raju, M. S. (Indian Journal of Marketing, 2019)
The emergence of social networking sites has gained popularity among people of different strata. Communication channels and modes faced a rapid change with the introduction of the World Wide Web in 1991. The review of literature rendered insights on communication as well as the role of trust in light of social exchange theory and social networking. The case study focused on the interaction among members in case of five Facebook groups during November-December 2017. Facebook groups like Karshika Vipani and Jaivakarshaka Koottayma established markets to sell organic products of small scale farmers. Facebook groups like Yuvakarshaka Kootayma, Krishi, and Jaivakeralam Karshika Group frequently shared information regarding their farming methods and tricks, farm products, and new methodologies of farming. All these gave a feeling of belongingness and strengthened the relationship among the members. Apart from sharing information, the members also formed seed banks to store and exchange seeds among the members of the groups. Moderators and active members interacted to conduct group meets in which the group members met physically. Constant communication and solid trust between the group members led to the formation of online offers and trades. Small farmers got a place to sell their products for a reasonable price at Sunday markets. Many of the farmers sold their products after value additions. The exchange of seeds and plants promoted agriculture and allied sectors. Constant demand and support encouraged a few members to become entrepreneurs. Frequent information transfer and trust contributed to the social exchange through Facebook groups.